2010
DOI: 10.1021/jf102120c
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Derived Peptide IRW Inhibits TNF-α-Induced Inflammatory Response and Oxidative Stress in Endothelial Cells

Abstract: Oxidative stress and vascular inflammatory response are key mediators of endothelial dysfunction that leads to cardiovascular diseases. A novel peptide, IRW, was previously characterized from egg protein with angiotensin converting enzyme inhibitory activity. The purpose of the study was to investigate the effects and molecular mechanisms of IRW on regulating inflammatory response in endothelial cells. The results showed that tumor necrosis factor-α (TNF-α) significantly increased the protein levels of interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 30 publications
10
88
0
1
Order By: Relevance
“…We found that IĸBα was almost completely (90–91% decrease) degraded within 15 min of TNF treatment in both E 2 -treated and -untreated cells. Even after 60 min, IĸBα levels were only partially (38–54%) replenished, in agreement with previous work from our group [53]. In contrast, IĸBβ remained unaffected by TNF stimulation in the untreated cells, while it was partially degraded (42–48% decrease) on prolonged TNF treatment (45 and 60 min) only in the E 2 -treated cells.…”
Section: Resultssupporting
confidence: 80%
“…We found that IĸBα was almost completely (90–91% decrease) degraded within 15 min of TNF treatment in both E 2 -treated and -untreated cells. Even after 60 min, IĸBα levels were only partially (38–54%) replenished, in agreement with previous work from our group [53]. In contrast, IĸBβ remained unaffected by TNF stimulation in the untreated cells, while it was partially degraded (42–48% decrease) on prolonged TNF treatment (45 and 60 min) only in the E 2 -treated cells.…”
Section: Resultssupporting
confidence: 80%
“…Some prior work has shown that peptides derived from egg white protein exhibited biological activity, including angiotensin converting enzyme (ACE) inhibitory activity (Fujita, Sasaki, et al, 1995), antioxidant activity (Davalos, Miguel, et al, 2004), mineral-binding activity (Samaraweera, Zhang, et al, 2011), anti-inflammatory activity (Huang, Chakrabarti, et al, 2010), antimicrobial activity (Gong, Kalina, et al, 2009), anticoagulation properties (Yu et al, 2011a(Yu et al, , 2011b and anticancer properties (Yi, Kim, et al, 2003). Our previous work also suggested that the egg protein hydrolysates displayed anti-diabetic activity against glucosidase activity (Yu et al, 2011a(Yu et al, , 2011b.…”
Section: Introductionmentioning
confidence: 97%
“…1, the whole egg digests significantly reduced the superoxide level in VSMCs, confirming egg as a potential antioxidant commodity. 20,27,28 Among the three fractions, F1 showed a significant higher antioxidant activity (p < 0.05) at 2.5 mg/mL compared to the untreated (Fig. 1).…”
Section: 22mentioning
confidence: 99%